Sistem Pendukung Keputusan Spesifikasi Biji Jagung Berkualitas Terbaik dengan Metode Multi Attribute Utility Theory - Chairul Imam; Julius Santony; Yuhandri (Jurnal KomtekInfo, 2018)
Farmers sell corn kernels in the company of PT Charoen Pokphan Indonesia Tbk Medan, corn kernels are used to mix feed ingredients to meet the protein values and nutrition of these feeds to be of high quality. The company PT Charoen Pokphan Indonesia Tbk Medan buys corn kernels to farmers by specifying the best quality corn kernels, so they know the total price of corn kernels is in accordance with the quality needed. This research determines the criteria of the best quality types of corn kernels and how to apply the Multi Attribute Utility Theory to decision support systems to determine the quality of corn kernels, to be able to help the company PT Charoen Pokphan Indonesia Tbk Medan in determining the quality of corn kernels. Based on the criteria set out in the company PT Charoen Pokphan Indonesia Tbk Medan to obtain the best quality corn kernels using grade 1 to grade 4 and ranking. The results of testing these methods are produced a decision on an alternative with a total value of 86.7%. So this method is needed to evaluate the determination of the best quality corn kernels to produce the best decisions